Party-Id dan Tendensi Politik Uang di Provinsi Bali: Studi Kasus Pilkada Bali Tahun 2018 - Kadek Dwita Apriani; Irhamna Irhamna (Badan Pengawas Pemilihan Umum, 2020)
The symptoms of weakening party-identification (party-id) has been a major phenomenon in Regional Elections in Indonesia. Through the electoral politics perspectives, the weakening of party-id has been identified as one of the factors which contributed to the increasing rate of vote buying at the grassroots level. In other words, the stronger the party-id, the lower the tendency of vote buying. This hypothesis was being tested in Bali, a province hat have the highest percentage of voters with party-id in Indonesia. This study used quantitative methods through surveys to 1080 respondents which proportionally spread across all districts in Bali, conducted in May 2018. The study suggests there is a signifiant correlation between party-id and vote buying tendency. Voters with higher party-id are having the higher chances in accepting vote buying.